Take Care of the 3 P's That Will Take Care of Your Business - J. J., Soundararaj (Ushus Journal of Business Management, 2010)
There has been a commendable change in the strategies being used by the business enterprises to make profit. The business enterprises all over the world are expected, or even compelled to have a situation whereby the motive of "maximisation of profits" has been replaced by "optimisation of profits".